Synthesis and Characterization of Some Ruthenium(III) Complexes of Semicarbazones Derived from 4-Aminoantipyrine - Singh, Lakshman; Gupta, Pravin; Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
In the present work, we describe a new series of ten ruthenium (III) complexes of semicarbazones derived from 4-aminoantipyrine and varions aryl aldehydes. The complexes have the general composition [Ru(L)Cl3]. All the complexes were character-' ized by chemical analysis, conductance, magnetic moment measurements, infrared and electronic spectra. The ligands behave as neutral tridentate (N,N,O) molecules. The complexes are six-coordinated octahedral.